No reservations : music from the motion picture soundtrack. - Glass, Philip; Pope, Conrad; Bublé, Michael; Pavarotti, Luciano; Tebaldi, Renata; Sutherland, Joan, 1926-2010.; Bergonzi, Carlo; Conte, Paolo, 1937-; Calleja, Joseph, 1977-; Gelato, Ray; Phair, Liz (New York, NY : Decca, 2007)
Contains fourteen songs featured in the motion picture "No Reservations," including "Sway," by Michael Bublé, "Cielo e Mar" by Luciano Pavarotti, and "Count on My Lover" by Liz Phair.
Truffles and quail / Conrad Pope -- Sway (Michael Bublé) -- Aida. Celeste Aida (Luciano Pavarotti) -- Gianni Schicchi. O mio babbino caro (Renata Tebaldi) -- Zoe & Kate watch video / Philip Glass -- La traviata. Libiamo né lieti calici (Joan Sutherland & Carlo Bergonzi) -- Via con me (Paolo Conte) -- Rigoletto. La donna è mobile (Joseph Calleja) -- Madam Butterfly. Un bel di (Renata Tebaldi) -- Zoe goes to the restaurant / Philip Glass -- La gioconda. Cielo e mar (Luciano Pavarotti) -- Mambo gelato (Ray Gelato) -- Turandot. Nessun dorma (Luciano Pavarotti) -- Count on my love (Liz Phair).
Principally opera excerpts ; score composed by Philip Glass.
Various performers.
Compact disc.
Various performers.
Sung English and Italian.
Keywords: Motion picture music; Operas -- Excerpts; Motion picture music; Operas -- Excerpts; Motion picture music